Semiotic Analysis of The Bangka Culture in The Film of "Martabak Bangka (2019)" - Mustari, Sarihul; Wirawanda, Yudha (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2022)
Purpose: This research purpose is to examine how the Bangka cultural meanings are represented in the film Martabak Bangka (2019) produced by Bersahaja Entertainment. This research uses Charles Sanders Peirce's semiotic theory to describe signs, objects, and interpretants. Methodology: The method used in this research is a qualitative method using a purposive sampling technique in order to determine the data sample. The data collection technique is used by using documentation and observation techniques. Results: This research found multicultural meanings in the Bangka culture and local wisdom of the Bangka people which are represented through the Campak Dance, Bangka Belitung Malay Zapin songs, Dambus art, Lempah Kuning, Martabak Bangka, Nganggung Sepintu Sedulang custom, and Songkok Resam. Applications/Originality/Value: This study compares with the previous research in examining Bangka's culture more deeply. The locations of the differences in this research are in the object of research, the analysis of the theory used, the measuring instruments, and the literatures in the research.